2021
DOI: 10.1002/hyp.14021
|View full text |Cite
|
Sign up to set email alerts
|

Observations of canopy storage capacity and wet canopy evaporation in a humid boreal forest

Abstract: Evaporation of intercepted rain by a canopy is an important component of evapotranspiration, particularly in the humid boreal forest, which is subject to frequent precipitation and where conifers have a large surface water storage capacity. Unfortunately, our knowledge of interception processes for this type of environment is limited by the many challenges associated with experimental monitoring of the canopy water balance. The objective of this study is to observe and estimate canopy storage capacity and wet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Canopy storage capacity is a major part of the water balance. Ochoa-Sánchez et al (2018) found that canopy storage of an Andean grassland can be around 2 mm, which is similar to tree canopy water storage determined by Hadiwijaya et al (2021). Most studies in current literature show that the greatest relative throughfall among land use types can be obtained in forests while the greatest stemflow, when the rainwater drips from the stems, occurs in grasslands (Sadeghi et al, 2020).…”
Section: Introductionmentioning
confidence: 52%
“…Canopy storage capacity is a major part of the water balance. Ochoa-Sánchez et al (2018) found that canopy storage of an Andean grassland can be around 2 mm, which is similar to tree canopy water storage determined by Hadiwijaya et al (2021). Most studies in current literature show that the greatest relative throughfall among land use types can be obtained in forests while the greatest stemflow, when the rainwater drips from the stems, occurs in grasslands (Sadeghi et al, 2020).…”
Section: Introductionmentioning
confidence: 52%
“…The same can be said of the use of a water stress factor η s set at a constant value of 1 (Table ). Peak evaporation was underestimated which could be due to the fact that interception was not simulated in the current implementation of the MEP model although it can amount to ≈20% of evaporation in boreal forests (Grelle et al., 1997; Hadiwijaya et al., 2021; Pomeroy et al., 1999). Evaporation early in the growing season was often overestimated, notably at deciduous temperate forest sites (Figures 1a–1c).…”
Section: Resultsmentioning
confidence: 99%
“…For the first approach, data for precipitation events fulfilling the following four requirements are used: (1) the duration of the event was more than 4 h, (2) the total precipitation exceeded 5 mm, (3) the canopy was dry prior to the event (no precipitation for 8 or 18 h if the previous event ended before midday or after midday, respectively), and (4) the duration of breaks in the rainfall during the event was no more than 2 h (similar procedure as presented by Hadiwijaya et al, 2020;Pypker et al, 2012). For the second approach, a precipitation event is defined as observed rainfall greater than 0.5 mm of rain, and no rain has fallen minimum 6 h prior to the beginning of the event (the same procedure as presented by Link et al, 2004).…”
Section: Interception Loss Estimation Using the Gash Modelmentioning
confidence: 99%
“…Forest evapotranspiration includes transpiration by the vegetation, evaporation from the soil and interception loss. Studies on canopy interception loss have been completed in a variety of forest types and climates; humid tropical rainforest (Asdak et al, 1998;Jetten, 1996;Lloyd et al, 1988), semi-arid coniferous forest (Motahari et al, 2013), Mediterranean deciduous and coniferous forest (Llorens & Domingo, 2007), temperate deciduous (Herbst et al, 2008;Hörmann et al, 1996) and temperate coniferous forests (Cisneros Vaca et al, 2018;Hadiwijaya et al, 2020;Klaassen et al, 1998;Link et al, 2004;Pypker et al, 2005;Ringgaard et al, 2014). Globally, forest interception is highly variable in time and space and can comprise a substantial evaporative loss (Gerrits et al, 2010;Klaassen et al, 1998;Pypker et al, 2012) and rates up to 60% of precipitation in temperate regions have been reported in extreme cases (Staudt et al, 2011).…”
mentioning
confidence: 99%